Improvement in Quality of Initial Fuel Usage in Power System of Republic of Belarus - B. M. Khroustalev; V. N. Romaniuk; Ya. N. Kovalev; V. D. Akeliev; N. A. Kolomytskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a potential, energy and economic efficiency of joint activities of enterprises of the Ministry of Energy sector and enterprises of the material sector of the economic complex of the Republic of Belarus on the basis of the methodology for intensive energy saving. Such calculated values as annual savings of natural gas in Belarus – up to 1 million tons of fuel equivalent, release investment for the Ministry of Energy – up to 1 billion USD, range for changes in electricity generation during a day - up to 1 GW with a specific consumption of fuel equivalent – 160 g/(kWh) have been determined while taking thermal technology of asphalt concrete mixture production and regulation of electricity generation as an example. Fuel saving system and investment return create preconditions for realization of the project by private investors.